Awareness, Attitude and Practices of Grade 10 Students Toward Environmental Stewardship - Reutotar, Jocelyn Bautista (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of this study was to assess the environmental awareness, attitudes towards environmental protection, and environmental practices of Grade 10 students. The study used a mixed-method sequential design and involved 150 students from three National High Schools in Zambales. The results showed that Grade 10 students had a good level of awareness about environmental protection laws (M=8.42, SD=1.63) and environmental stewardship promotion (M=8.58, SD=1.42). They were supportive of community environment protection (M=3.33) and school environment protection (M=3.46). However, the students observed improper waste segregation in both the school and community, leading to an increased interest in promoting environmental protection activities. There was a moderate positive correlation between the students' level of awareness on environmental protection and stewardship promotion and their environmental practices. Similarly, there was a moderate positive correlation between their environmental attitude in the community and school and their environmental protection practices. The Grade 10 students who are aware of the importance of protecting the environment and promoting ecological stewardship tend to be more concerned about conserving energy and natural resources. They are also supportive of activities aimed at protecting their school and community environments, and are observant of environmental problems in these areas. The study found that students' awareness and attitudes towards environmental protection and ecological stewardship have a positive impact on their practices to conserve and protect the environment. The study recommends that schools and communities should involve students in environmental protection activities to encourage their support for conserving energy and natural resources.